2010
DOI: 10.1021/ja908477w
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reactions of Ozone with Surfactant Protein B in a Model Lung Surfactant System

Abstract: Oxidative stresses from irritants such as hydrogen peroxide and ozone (O3) can cause dysfunction of the pulmonary surfactant (PS) layer in the human lung, resulting in chronic diseases of the respiratory tract. For identification of structural changes of pulmonary surfactant protein B due to the heterogeneous reaction with O3, field induced droplet ionization (FIDI) mass spectrometry is utilized. FIDI is a soft ionization method in which ions are extracted from the surface of microliter-volume droplets. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 55 publications
(114 reference statements)
6
67
2
Order By: Relevance
“…In earlier FIDI studies of the oxidation of lipid mixtures by ozone it was observed that eventually the products from oxidized unsaturated lipids were dissolved back into solution, leaving a surface layer dominated by unreactive saturated lipids. 26 are much lower than other products discussed above (Figures 1 and 4) where no bond cleavage occurs; they amount to approximately 4% of the total product yield. The major m/z 171 peak is a result of the C=C bond cleaved into an aldehyde group, and the peaks at higher m/z can be accounted for as oxidation products of the nascent aldehyde product.…”
Section: Oxidation Product Analysis By Mass Spectrometrymentioning
confidence: 57%
“…In earlier FIDI studies of the oxidation of lipid mixtures by ozone it was observed that eventually the products from oxidized unsaturated lipids were dissolved back into solution, leaving a surface layer dominated by unreactive saturated lipids. 26 are much lower than other products discussed above (Figures 1 and 4) where no bond cleavage occurs; they amount to approximately 4% of the total product yield. The major m/z 171 peak is a result of the C=C bond cleaved into an aldehyde group, and the peaks at higher m/z can be accounted for as oxidation products of the nascent aldehyde product.…”
Section: Oxidation Product Analysis By Mass Spectrometrymentioning
confidence: 57%
“…Exposure of mixed monolayers composed of POPC and DPPC to ozone does not lead to a loss of DPPC from the air-water interface, but surface activity changes significantly secondary to oxidative damage of the unsaturated POPC [32]. Similar findings have been reported for the shorter SP-B mimic SP-B 1–25 in unsaturated 1-palmitoyl-2-oleoyl-sn-glycerol [33]. Both components were affected by exposure to ozone resulting in reduced surface activity at the air-water interface.…”
Section: Discussionmentioning
confidence: 54%
“…Field-induced droplet ionization mass spectrometry (FIDI-MS) employs a soft ionization technique to sample ions from the surface of microliter liquid droplets to a mass analyzer [12][13][14][15]. Utilizing FIDI-MS, several studies of time-resolved heterogeneous reactions at air-liquid interfaces have been reported [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing FIDI-MS, several studies of time-resolved heterogeneous reactions at air-liquid interfaces have been reported [14,15]. For example, the location and orientation of SP-B 1-25 (a shortened version of human surfactant protein B) in a lipid surfactant layer has been deduced from experimentally observed reactivity with ozone (O 3 ) using a FIDI-MS methodology [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation